2019
DOI: 10.1186/s13024-019-0329-1
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein structure and Parkinson’s disease – lessons and emerging principles

Abstract: Alpha-synuclein (αS) is the major constituent of Lewy bodies and a pathogenic hallmark of all synucleinopathathies, including Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA). All diseases are determined by αS aggregate deposition but can be separated into distinct pathological phenotypes and diagnostic criteria. Here we attempt to reinterpret the literature, particularly in terms of how αS structure may relate to pathology. We do so in the context of a rapidly evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
254
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 318 publications
(257 citation statements)
references
References 107 publications
3
254
0
Order By: Relevance
“…Recent structural studies suggest that C‐terminal truncation could modulate the structure of αsyn fibrils such that a species barrier‐like phenomenon could develop in which seeding of FL mouse αsyn by C‐truncated forms of αsyn would be impaired . To assess this hypothesis using the previous HEK293T cell experimental paradigm, mPFFs comprised of C‐terminally truncated αsyn were treated to cells expressing FL mouse αsyn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent structural studies suggest that C‐terminal truncation could modulate the structure of αsyn fibrils such that a species barrier‐like phenomenon could develop in which seeding of FL mouse αsyn by C‐truncated forms of αsyn would be impaired . To assess this hypothesis using the previous HEK293T cell experimental paradigm, mPFFs comprised of C‐terminally truncated αsyn were treated to cells expressing FL mouse αsyn.…”
Section: Resultsmentioning
confidence: 99%
“…These studies show that αsyn fibrils are C‐truncated upon entry to neurons and other cells; thus, the predominant pathologic αsyn species in early neuronal seeding events are heavily C‐truncated. Recent structural studies suggest that C‐terminal truncation changes the structure of αsyn fibrils , and likewise, experiments utilizing various models have demonstrated functional consequences for seeding with different C‐truncated forms of human αsyn .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha‐synuclein (α‐syn), composed of 140 amino acids, is expressed in the presynaptic and perinuclear regions of the central nervous system (Meade, Fairlie, & Mason, ). Studies have shown that under normal physiological conditions, α‐syn is low‐expression, soluble protein associated with dopamine uptake, synaptic plasticity, and vesicle maintenance (Sulzer & Edwards, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in order to investigate key mechanistic or functional processes, successful isolation of different α‐Syn species is imperative. As with some other amyloid‐forming proteins, α‐Syn possesses a unique structural polydispersity whereupon the unstructured monomer can adopt a helical conformation when interacting with membranes, or β‐sheet structure when forming fibrils (Meade, Fairlie, & Mason, ).…”
mentioning
confidence: 99%